Application of capillary electrophoresis in the analysis of coloring matter on paper - Król, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Modern law enforcement agencies are constantly struggling with crimes against documents. Due to increasing quality of counterfeit documents and different physicochemical properties of inks, such crimes are becoming harder to detect. This situation obliges forensic laboratories for the development and implementation of testing procedures with the use of some modern techniques of chemical analysis.CE opens up numerous possibilities for various analytical applications, mainly due to its numerous advantages, the diversity of its modes and the compatibility with different detection systems. This study focuses on discussing two modes of CE: CZE and MECC and three different detection systems: DAD, LIF and MS. By using them information about substances exhibiting absorption, fluorescence and about molecular mass of analyzed compound can be received. In the Laboratory for Forensic Chemistry many different coloring matters were examined, including ballpoint, fountain pen, gel and stamp pad inks in most popular colors as well as a large group of branded and off-brand printing inks.The obtained results showed the great applicability of CE-DAD method. It has been proved that LIF and MS detections improve the discriminating possibilities of CE providing additional information on samples.
Keywords: dokument; fałszerstwo; elektroforeza kapilarna; chemia analityczna; dyskryminacja